Pemulihan Industri Pariwisata di Kota Makassar Pasca Pandemi COVID-19 - Regina; Irwandi; Annisa Paramaswary Aslam; Basalamah, Muhammad Syafi'i A. (Fakultas Ekonomi, Universitas Muslim Indonesia, 2025)
This research employs a literature study method focused on the revitalization of the tourism industry in Makassar during the Covid-19 pandemic. The data used are derived from nationally and internationally recognized sources. The study was conducted through manual research, utilizing data collected from Google Scholar and Mendeley to address information gaps related to the challenges faced by the tourism sector before and after the pandemic. The impact of Covid-19 on the population of Makassar City is evident in the significant decline in both international and domestic travel. The number of tourist visits—both domestic and foreign—decreased substantially. A crucial first step in improving employment conditions in the tourism sector is addressing issues in the transportation sector, including the availability of lodging and food services. The Covid-19 pandemic severely disrupted the national economy. Tourism, which plays an essential role in human life as a means to relieve stress and fatigue from work, was among the most affected sectors. Various economic analyses have shown that tourism was one of the hardest-hit industries. While tourism has the potential to support the broader community economy, the overall economic downturn has negatively impacted the tourism sector at both macro and micro levels.